The Enigma of Substrate Recognition and Catalytic Efficiency of APE1-Like Enzymes - Davletgildeeva, Anastasiia T.; Ishchenko, Alexander A.; Saparbaev, Murat; Fedorova, Olga S.; Kuznetsov, Nikita A. (Frontiers in Cell and Developmental Biology, 2021)
Despite significant achievements in the elucidation of the nature of protein–DNA contacts that control the specificity of nucleotide incision repair apurinic/apyrimidinic (AP) endonucleases, the question how a given nucleotide is recognized by the active site of the enzyme remains unanswered. Therefore, the main purpose of our study was to compare kinetics of conformational changes of three homologous APE1-like endonucleases (insect Drosophila melanogaster Rrp1, amphibian Xenopus laevis xAPE1, and fish Danio rerio zAPE1) during their interaction with various damaged DNA substrates, i.e., DNA containing an F-site (an uncleavable-by-DNA-glycosylases analog of an AP-site), 1,N6-ethenoadenosine, 5,6-dihydrouridine, uridine, or the α-anomer of adenine. Pre–steady-state analysis of fluorescence time courses obtained for the interaction of the APE1-like enzymes with DNA substrates containing various lesions allowed us to outline a model of substrate recognition by this class of enzymes. It was found that the differences in rates of DNA substrates’ binding do not lead to significant differences in the cleavage efficiency of DNA containing a damaged base, suggesting that the formation of enzyme–substrate complexes is not the key factor that limits the enzyme turnover. The results suggest that the fine conformational tuning inside the active site must be the driving force behind the processes catalyzed by APE1-like enzymes.